MODEL DINAMIKA PENYEBARAN PENYAKIT CAMPAK DENGAN PENGARUH VAKSINASI DAN PENERAPANNYA DI PROVINSI NUSA TENGGARA BARAT - ,, MUTMAINNAH; AWALUSHAUMI, LAILIA; AINI, QURRATUL (E-Jurnal Matematika, 2019)
Measles is an acute disease highly contagious, caused the measles. This disease is transmitted through droplet or direct contact to the patient. Besides causing various complications, this disease can also cause death. The purpose of this research was we formulated a model the dynamics of the spread of diseases by the influence of a measles vaccination, that are used to know the influence of vaccination to the spread of diseases measles in the province of NTB. The dynamics model of the spread of diseases by the influence of a measles vaccination, Based on a implementation model in NTB Province we get bigger the scope of vaccination done in the NTB so the less individuals are susceptible when stability and measles disease faster disappearance.